식품 소비 라이프스타일이 간편식의 구매 경험, 만족도, 구매 의향에 미치는 영향: HMR 유형별 매개효과와 조절효과를 중심으로 - 한은수; Han Eun-su; 윤병삼; Yoon Byung-sam; 서상택; Seo Sang-taek (농촌경제, 2024)
본 연구는 식품 소비 라이프스타일이 HMR 구매 경험 및 만족도, 구매 의향에 미치는 영향 관계에 대한 직접효과(direct effects) 및 매개효과(mediation effects)를 분석하였다. 또한, HMR 제품 유형별 구매 빈도가 높은 상위 집단과 빈도가 낮은 하위집단을 분류하여 집단 간 차이 검정에 의한 조절효과(moderation effects)를 분석하였다. 분석 결과, 간편성 추구형은 HMR 구매 경험과 만족도에 유의한 정(+)의 영향을 미치는 것으로 나타났다. 구매 의향에 대해서는 직접효과가 없었으나, 구매 경험과 만족도를 경유하는 매개효과가 있는 것으로 분석되었다. 건강·안전 추구형은 HMR 구매 경험과 구매 의향에 부(-)의 영향 또는 유의한 영향 관계가 없는 것으로 나타났다. 그러나 HMR 구매 만족도에 유의한 정(+)의 영향을 미치는 것으로 나타났고, 조절효과 검정을 통해 구매 빈도가 낮은 집단의 만족도가 높은 것으로 분석되었다. 경제성 추구형은 즉석조리식품과 즉석섭취식품에 있어서 구매 경험, 만족도, 구매 의향에 대해 유의한 정(+)의 영향을 미쳤고, 직접효과와 매개효과가 있는 것으로 확인하였다. This study analyzed the direct effects and mediation effects of the food consumption lifestyle on HMR purchase experience, satisfaction, and purchase intention. In addition, the moderation effects between groups were analyzed by classifying the upper group with high purchase frequency and the lower group with low frequency by HMR product type. It was found that the convenience seeking type had a significant positive (+) effect on HMR purchase experience and satisfaction. There was no direct effect on the purchase intention, but it was analyzed that there was a mediating effect through purchase experience and satisfaction. The health and safety seeking type was found to have no negative (-) or significant effect on HMR purchase experience and purchase intention. However, it was found that it had a significant positive (+) effect on HMR purchase satisfaction, and it was analyzed that the satisfaction of the group with low purchase frequency was high through the moderation effects. The economic seeking type had a significant positive (+) effect on purchase experience, satisfaction, and purchase intention in instant cooked and instant foods, and was confirmed to have direct and mediating effects.